Management Plan for the Development of the Radya Pustaka Museum as a Cultural and Educational Tourism in Surakarta City - Wibiyanto, Agung; Resmi, Prasiwi Citra; Syaifullah, Jahid; Juliansyah, Irvan (Universitas Syiah Kuala, 2024)
The purpose of this study is to review the internal and external factors of the management of the Radya Pustaka museum and also to analyze the management design in the development of the Radya Pustaka museum as a cultural and educational tourism in the city of Surakarta. This research method is a qualitative method, where the data obtained is analyzed based on the internal and external factors of the Radya Pustaka museum which are formulated in the IFAS and EFAS matrix indicators. The results of the analysis are described in a SWOT analysis. The results of this study are that the existence of the Radya Pustaka Museum as a cultural heritage tourist attraction is in a moderate or average position. From the internal-external environmental analysis method, the strategy that must be applied by objects in cell V is to maintain and preserve (unchanged strategy). The object operates with moderate appeal and only has an average competitive position. The strategy carried out is to continue its current activities and only make a few improvements.Keywords: Management, Radya Pustaka Museum, cultural and educational tourism